2001
DOI: 10.1108/09513550110395256
|View full text |Cite
|
Sign up to set email alerts
|

Public sector reform – Implications for accounting, accountability and performance of state‐owned entities – an Australian perspective

Abstract: Faced by increased globalization, the dissatisfaction of Australian citizens, and a curtailing of spending, the Australian Government has embarked on a major reform agenda centered on new public management ideals to achieve greater economy, efficiency, and effectiveness. A major driver of reform in all levels of government has been the introduction of the national competition policy. Describes the recent developments in Australian public sector and discusses reform implications for accounting, accountability a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
85
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(85 citation statements)
references
References 15 publications
0
85
0
Order By: Relevance
“…In Australia, the changes were facilitated through financial and legislative reforms enacted through the Public Service and Workplace Relations Acts (Anderson et al, 2002b). Curtin (2000) contends that the search for cost efficient outcomes jeopardized the key pillars of the public sector by shifting the focus to customers (Hoque and Moll, 2001), intensifying public scrutiny and creating fluid performance expectations, thus increasing political interference (Caverley, 2005). Such interactions exerted pressures on public sector managers to deliver outcomes, changing work and performance dynamics, and ultimately affecting workplace interactions.…”
Section: Ecology Of the Sectormentioning
confidence: 99%
“…In Australia, the changes were facilitated through financial and legislative reforms enacted through the Public Service and Workplace Relations Acts (Anderson et al, 2002b). Curtin (2000) contends that the search for cost efficient outcomes jeopardized the key pillars of the public sector by shifting the focus to customers (Hoque and Moll, 2001), intensifying public scrutiny and creating fluid performance expectations, thus increasing political interference (Caverley, 2005). Such interactions exerted pressures on public sector managers to deliver outcomes, changing work and performance dynamics, and ultimately affecting workplace interactions.…”
Section: Ecology Of the Sectormentioning
confidence: 99%
“…Accrual accounting has been criticised because it enables organizations to defer liabilities and burden future taxpayers with these costs (Hoque & Moll, 2001). When it comes to the valuation of infrastructure assets for balance sheet purposes, the determination of these assets' economic value and economic life is problematic because the assets are usually very large and their life may be extended indefinitely when they are irreplaceable or provide essential services (Pallot, 2000).…”
Section: Stakeholders and Accounting Informationmentioning
confidence: 99%
“…Halligan (2004) noted that by the mid-1990s, market principles were the central element and competition and contestability became the currency of reform. Hoque and Moll (2001) mentioned that a range of social, economic and technological pressure was responsible for forcing the governments to become more effective, efficient and accountable for the use of publicly generated funds.…”
Section: Financial Management Improvement Programmentioning
confidence: 99%
“…The NCP suggested that if the public sector entities are to become more economic, efficient and effective they should be operating according to the same commercial principles as applied in the private sector (Hoque and Moll, 2001). Implementing the private sector tools in the public sector also requires developing the new management focus.…”
Section: The National Competition Policymentioning
confidence: 99%